Global Rural-Urban Mapping Project (GRUMP) - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
The data contained here are a preliminary version of the Urban-Rural urban mask. Improved versions will follow. All urban areas with a population of 1,000 persons or more have been included. Note that for many countries, the data collection did not include settlements as small as 1,000 persons. Ancillary information indicating the smallest settlement size is forthcoming. No population values are given here, but will be available in complementary data products.; Demographic information is often provided on a national basis, but global environmental and other cross-disciplinary studies usually require data that are referenced by geographic coordinates, such as latitude and longitude, rather than by political or administrative units. In this dataset, the distribution of human population is converted from national or subnational units to a series of eoreferenced quadrilateral grids.; Developed in 1999-2000, GPW version 2, incorporates a number improvements to the original version of this popular dataset. GPW version 2 provides estimates of the population of the world in 1990 and 1995, both population counts (raw counts) and population densities (per square km). National figures have been reconciled to be consistent with United Nations population estimates for those years; unadjusted data are also available. Both images and data are downloadable.